2018
DOI: 10.3390/min8070267
|View full text |Cite
|
Sign up to set email alerts
|

Lunar and Martian Silica

Abstract: Silica polymorphs, such as quartz, tridymite, cristobalite, coesite, stishovite, seifertite, baddeleyite-type SiO2, high-pressure silica glass, moganite, and opal, have been found in lunar and/or martian rocks by macro-microanalyses of the samples and remote-sensing observations on the celestial bodies. Because each silica polymorph is stable or metastable at different pressure and temperature conditions, its appearance is variable depending on the occurrence of the lunar and martian rocks. In other words, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 175 publications
(314 reference statements)
0
19
0
2
Order By: Relevance
“…This inference is supported by the tweed‐like texture of the host silica fragment (El Goresy et al., 2004). Alpha‐cristobalite is one of the common SiO 2 phases in lunar materials (Kayama et al., 2018) and transforms to stishovite, seifertite, and high‐pressure glass during impact events (Miyahara et al., 2013). Therefore, α‐cristobalite could be the precursor of α‐cristobalite‐like phase, seifertite, and stishovite in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This inference is supported by the tweed‐like texture of the host silica fragment (El Goresy et al., 2004). Alpha‐cristobalite is one of the common SiO 2 phases in lunar materials (Kayama et al., 2018) and transforms to stishovite, seifertite, and high‐pressure glass during impact events (Miyahara et al., 2013). Therefore, α‐cristobalite could be the precursor of α‐cristobalite‐like phase, seifertite, and stishovite in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Organic inclusions in quartz of hydrothermal origin found in Archean rocks from Western Australia also suggest that this mineral could play an important role in molecular evolution leading to the emergence of life on our planet. [17] Further, quartz is a frequent mineral on other celestial bodies, [18] and can be found in meteorites. [16,19] Actually, the catalytic role of silica surfaces has been investigated in a series of important prebiotic processes.…”
Section: Global-scale Oligonucleotide Production Due To Cgmp-h Polymerization On the Early Earthmentioning
confidence: 99%
“…The other polymorphs, including tridymite, coesite, and stishovite, are less frequently found in nature, thus the relevance of their impact on human health is minor. Nonetheless, deposits of terrestrial and celestial rare CS polymorphs were recently reported ( Roskosz and Leroux, 2015 ; Morris et al, 2016 ; Kayama et al, 2018 ), hence our study might help to evaluate the hazard of also these rare CS polymorphs in future exploration and possible exploitations. Finally, the comprehension of the surface characteristics and reactivity of CS polymorphs here described could provide further hints for explaining complex bio-mineral interfacial phenomena, including prebiotic chemistry reactions ( Rimola et al, 2018 ; Rimola et al, 2019 ) and a variety of heterogeneous atmospheric processes ( Sihvonen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 87%